2009
DOI: 10.1111/j.1468-0408.2008.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Charities: An Exploration of Key Themes and the Development of a Research Agenda

Abstract: The concept of governance has been widely discussed in both the business and non‐business sectors. The debate has also been entered into within the charity sector, which comprises over 169,000 organizations in the UK. The UK‐based Charity Commission, which describes itself as existing to ‘promote sound governance and accountability’, has taken a lead in this debate by promoting greater regulation and producing numerous recommendations with regard to the proper governance of charitable organizations. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
209
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(212 citation statements)
references
References 35 publications
1
209
1
1
Order By: Relevance
“…2 Papers in the last 10 years that provide good overviews of the non-profit governance literature include Hyndman and McDonnell (2009), Ostrower (2007), Miller-Millesen (2003), Green et al (2001), Ostrower and Stone (2001), Murray and Cutt (2000), and Stone et al (1999). Academic papers view board performance through a variety of perspectives, including Agency Theory, Resource Dependence, Institutional Theory, and Transaction Cost models.…”
Section: Literature Review and Development Of Empirical Hypotheses Anmentioning
confidence: 98%
“…2 Papers in the last 10 years that provide good overviews of the non-profit governance literature include Hyndman and McDonnell (2009), Ostrower (2007), Miller-Millesen (2003), Green et al (2001), Ostrower and Stone (2001), Murray and Cutt (2000), and Stone et al (1999). Academic papers view board performance through a variety of perspectives, including Agency Theory, Resource Dependence, Institutional Theory, and Transaction Cost models.…”
Section: Literature Review and Development Of Empirical Hypotheses Anmentioning
confidence: 98%
“…123) also examined the effectiveness of nonprofit regulation in the US and found that the Nonprofit Integrity Act (NIA) of 2004 had the "effect of increasing accounting fees, while providing limited improvement in financial reporting quality in the first year of implementing the Act." Hyndman and McDonnell (2009;see also Cordery, 2013) posit that charities may become more accountable to the regulator at the expense of their donors and beneficiaries. Onerous reporting requirements can force charities to divert time and resources away from achieving objectives (Szper & Prakash, 2011) and discourage innovation (Johnson et al, 1998).…”
Section: Literaturementioning
confidence: 99%
“…These include donors, the accounting profession, regulators, beneficiaries, government and the public (Hyndman and McDonnell, 2009). This array of stakeholders presents charities with complex and often competing needs to meet (Codery and Baskerville, 2011).…”
Section: To Whom and What Motivates Charity Accountability?mentioning
confidence: 99%